The Importance of Tutors' Instructional Practices: Evidence from a Norwegian Field Experiment - Hans Bonesrønning; Jon Marius Vaag Iversen (Center for Economic Studies and ifo Institute (CESifo), 2024)
We use data from a large field experiment where young students were pulled out of their regular classes and offered mathematics instruction in small homogenous groups, to investigate the importance of the tutors' instructional practices. The analyzes are limited to low achievers, and the instructional practices are characterized by the degree of individualization and the tutors' allocation of attention between students. Tutors who spent much time with avoidant students were associated with a treatment effect of approximately 0.20 SD while tutors who spent little time with these students were associated with no significant treatment effects.
Keywords: I20; I21; 330; tutoring; tutor quality